HUBUNGAN AKTIVITAS FISIK DENGAN FUNGSI KOGNITIF PADA LANSIA DI PERUMAHAN VILLA BALARAJA - Cici Susanti (2021)
Background: Aging can cause changes in sensory perception of the central nervous system and motor responses, as well as a decrease in proprioceptive responses. These changes in the nervous system can lead to a decline in cognitive function in old age. Physical activity can affect and provide benefits to cognitive function in old age, and can prevent cognitive dysfunction. Objective: This study was to determine the relationship between physical activity and cognitive function of the elderly in Villa Balaraja Housing. Methods: this study used a descriptive correlational method. The research design was cross-sectional. Measuring instruments: Physical activity will be measured using the International Physical Activity Questionnaire version of the Short-Form (IPAQ-SF) and Cognitive function measurement using the Mini Mental Status Examination (MMSE) (Mini Mental State Examination (MMSE) questionnaire. Data result: The data obtained in the Chi-Square test is p = 0.020 which is smaller than the significant standard (α: 0.05). Conclusion: there is a significant relationship between physical activity and cognitive function in the elderly at Villa Balaraja Housing.